2017
DOI: 10.1063/1.4982939
|View full text |Cite
|
Sign up to set email alerts
|

Dibromobianthryl ordering and polymerization on Ag(100)

Abstract: We study the interaction between dibromobianthryl (DBBA) and the Ag(100) surface using scanning tunneling microscopy and density functional theory. DBBA is prochiral on adsorption and forms racemic domains with molecular rows aligned with the substrate nearest-neighbor [011] and [011] directions. Deposition at elevated temperature leads to the formation of disordered meandering graphene nanowires of constant width.⇤ jsmerdon@uclan.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
3
3
Order By: Relevance
“…4a has the energy of the metal-bonded component, indicating that the molecule debrominates upon adsorption at RT. The higher temperature sequence shows that Br is stable on the surface up to T = 200 • C. Debromination below RT has also been observed for DBBA on Cu(110) 40 and Cu(111), 34 but our observation is in contrast to that reported for Ag(100), 55 where the authors concluded that DBBA adsorbed intact based on the absence of Br atoms in STM images. The C 1s spectrum obtained at RT can only be fitted by reducing the C-H/C-C ratio well below the values of the intact precursor and adding a C-Ag component, suggesting that both debromination and partial dehydrogenation has taken place simultaneously, and that C radicals are saturated by metal coordination (see Fig.…”
Section: Xps Spectra Obtained After Deposition At Rt Reveal a Lower Dcontrasting
confidence: 71%
See 3 more Smart Citations
“…4a has the energy of the metal-bonded component, indicating that the molecule debrominates upon adsorption at RT. The higher temperature sequence shows that Br is stable on the surface up to T = 200 • C. Debromination below RT has also been observed for DBBA on Cu(110) 40 and Cu(111), 34 but our observation is in contrast to that reported for Ag(100), 55 where the authors concluded that DBBA adsorbed intact based on the absence of Br atoms in STM images. The C 1s spectrum obtained at RT can only be fitted by reducing the C-H/C-C ratio well below the values of the intact precursor and adding a C-Ag component, suggesting that both debromination and partial dehydrogenation has taken place simultaneously, and that C radicals are saturated by metal coordination (see Fig.…”
Section: Xps Spectra Obtained After Deposition At Rt Reveal a Lower Dcontrasting
confidence: 71%
“…4a has the energy of the metal-bonded component, indicating that the molecule debrominates upon adsorption at RT. The higher temperature sequence shows that Br is stable on the surface up to T = 200 • C. Debromination below RT has also been observed for DBBA on Cu(110) 40 and Cu(111), 34 but our observation is in contrast to that reported for Ag(100), 55 where the authors concluded that DBBA adsorbed intact based on the absence of Br atoms in STM images. 111).…”
Section: Ag(100): From Non-planar To Aromatic Metal Coordinated Polymerscontrasting
confidence: 71%
See 2 more Smart Citations
“…Correspondingly, differences in the organometallic intermediates are expected on the two Ag lattices, if the lattice registry of Ag adatoms drives the structure oft he organometallic overlayers. At present, a majority of on‐surface synthesis reactions on Ag are reported on the (111) facet, although Ullmann‐type coupling also successfully proceeds on Ag(110) and Ag(100) surfaces. Therefore, this study will provide further interesting insights into Ullmann‐type reactions on Ag(100), which has rarely been addressed although the Ullmann‐type reaction is a workhorse in on‐surface synthesis.…”
Section: Introductionmentioning
confidence: 99%